Amniotic bands in connective tissue disorders. - Young, I D (1985)
Amniotic bands are described in two children with Ehlers-Danlos syndrome type IV and in one with severe osteogenesis imperfecta. Since the basic defect in both of these disorders rests in collagen, which constitutes the main component of the load bearing amnion, it is proposed that these cases provide further insight into the pathogenesis of amniotic bands.